100k views
0 votes
-5x + y = -3 and –x - 5y = - 11 by substitution​

User Corlaez
by
5.8k points

2 Answers

3 votes

Answer:

Required Answer:-

  • -5x+y=-3---------------(1)
  • -x-5y=-11----------------(2)

From eq (1)


{:}\longrightarrow
\sf -5x+y=-3


{:}\longrightarrow
\sf y=-3+5x


{:}\longrightarrow
\sf y=5x-3\dots\dots (3)

  • Substitute the value in eq (2)


{:}\longrightarrow
\sf -x-5 (5x-3)=-11


{:}\longrightarrow
\sf -x-25x+15=-11


{:}\longrightarrow
\sf -26x=-11-15


{:}\longrightarrow
\sf -26x=-26


{:}\longrightarrow
\sf x={\frac {-26}{-26}}


{:}\longrightarrow
\sf x=1

  • Substitute the value in eq (3)


{:}\longrightarrow
\sf y=5x-3


{:}\longrightarrow
\sf y =5 (1)-3


{:}\longrightarrow
\sf y=5-3


{:}\longrightarrow
\sf y=2


\therefore(x,y)=(1,2)

User Mangrio
by
6.6k points
4 votes

Answer:

x = 1, y = 2

Explanation:

-5x + y = -3, we get y = 5x - 3.

Then plugs into the second equation, we get

-x - 5 (5x-3) = -11.

-x - 25x + 15 = -11,

-26x = -26

x = 1,

plugs x = 1 to y = 5x - 3, we get y = 2.

User Jan Slominski
by
5.6k points